Adelante Mujeres! history of Mexican-American women - Ruthsdotter, Mary.; Cuevas, Maria Elena; Ruiz, Vicki; National Women's History Project (Windsor, CA : National Women's History Project, 2000)
Presents the history of Mexican-American/Chicana women, emphasizing major themes, organizations, and personalities over five centuries. Includes hundreds of photographs that portray the strengths and resilience of Mexican American/Chicana women as the centers of their families, activists in their communities, and contributors to American history.
Narrators, Maria Elena Cuevas, Cristina Briano, Jessie Lopez de la Cruz, Martha Cortera.
DVD
English
No Master.
Keywords: Mexican American women -- History; Mexican American women -- Social conditions; Mexican American women -- Political activity